Contrasting effects of partial organic substitution and its inoculation with phosphate-solubilizing bacteria on stoichiometric imbalances and phosphorus fractions accumulation after six-year application in a rice paddy - Xinxin You; Wenyi Xu; Linna Du; Sheng Wang; Yan Zhou; Xiaomin Ma; Hua Qin; Junhui Chen (Soil and Tillage Research, 2026)

Enhancing the whipping properties of blend whipped cream using coconut diglyceride through crystallization modulation and interfacial stabilization - Huijie Dong; Chonghao Wang; Fengyan Wang; Linna You; Yan Chen; Shangde Sun (Food Chemistry, 2026)

Flexural performance of CFRP grid-reinforced ultra-high performance concrete (UHPC) plates under cyclic incremental loading - JinJing Liao; Haotian Li; Yu Zheng; Linna Geng; Yan Zhuge; Jun-Jie Zeng (Engineering Structures, 2026)

Genome-wide identification of NF-Y family in Carya illinoinensis and CiNF-YC6 role in fatty acid biosynthesis - Linna Wang; Lina Zou; Zixian Yao; Jinhua He; Shunran Zhang; Yan Xiang (Plant Cell Reports, 2026)

Identification of the bHLH transcription factor family and functional characterization of CibHLH141 and CibHLH127 in response to iron deficiency stress of pecan (Carya illinoinensis) - Lina Zou; Linna Wang; Jinhua He; Zixian Yao; Shunran Zhang; Yan Xiang (Plant Science, 2025)

Compartment-specific core microbiomes and functions in rice - Linna Ma; Yusha Bai; Xiang Li; Jingyu Li; Feixue Li; Yan Yue; Yingguang Li; Jingwen Guo; Chen Ye; Xinyue Mei; Fei Du; Yixiang Liu; et al. (Plant and Soil, 2025)

Functional carbon nanodots enhance tomato tolerance to zinc deficient soils: Mechanisms and structure-function relationships - Qiong Chen; Guling Xing; Xiufeng Cao; Taibo Liang; Lijuan Chen; Linna Dai; Lijie Ci; Mei Yan (Science of The Total Environment, 2024)

CiAP2/ERF65 and CiAP2/ERF106, a pair of homologous genes in pecan (Carya illinoensis), regulate plant responses during submergence in transgenic Arabidopsis thaliana - Hongxia Liu; Yangang Lan; Linna Wang; Nianqin Jiang; Xiaoyue Zhang; Min Wu; Yan Xiang (Journal of Plant Physiology, 2024)

Genome-wide identification of the Carya illinoinensis bZIP transcription factor and the potential function of S1-bZIPs in abiotic stresses - Nianqin Jiang; Linna Wang; Yangang Lan; Hongxia Liu; Xiaoyue Zhang; Wei He; Min Wu; Hanwei Yan; Yan Xiang (Tree Genetics & Genomes, 2023)

Assessing nickel sector index volatility based on quantile regression for Garch and Egarch models: Evidence from the Chinese stock market 2018–2022 - Linna Lu; Yalin Lei; Yang Yang; Haoqi Zheng; Wen Wang; Yan Meng; Chunhong Meng; Liqiang Zha (Resources Policy, 2023)

PheLBD29, an LBD transcription factor from Moso bamboo, causes leaf curvature and enhances tolerance to drought stress in transgenic Arabidopsis - Min Wu; Wei He; Linna Wang; Xiaoyue Zhang; Kang Wang; Yan Xiang (Journal of Plant Physiology, 2023)

Comparative genomic analysis of the CPK gene family in Moso bamboo (Phyllostachys edulis) and the functions of PheCPK1 in drought stress - Min Wu; Hongxia Liu; Linna Wang; Xiaoyue Zhang; Wei He; Yan Xiang (Protoplasma, 2023)

Identification and Expression Analysis of LBD Genes in Moso Bamboo (Phyllostachys edulis) - Yameng Gao; Kang Wang; Ruijia Wang; Linna Wang; Hongxia Liu; Min Wu; Yan Xiang (Journal of Plant Growth Regulation, 2022)

Identification of TCP family in moso bamboo (Phyllostachys edulis) and salt tolerance analysis of PheTCP9 in transgenic Arabidopsis - Yuzeng Xu; Linna Wang; Hongxia Liu; Wei He; Nianqin Jiang; Min Wu; Yan Xiang (Planta, 2022)

Study of the protective effects of cosmetic ingredients on the skin barrier, based on the expression of barrier-related genes and cytokines - Wenyu Ding; Linna Fan; Yan Tian; Congfen He (Molecular Biology Reports, 2022)
Background Sensitive skin is the result of a complex process that is closely linked to the damage of the skin barrier. There are no recognized methods for evaluating the efficacy of anti-allergy products. Methods In this study, a model of skin barrier damage was created by treating HaCaT cells with 60 μg/ml of sodium dodecyl sulfate for 48 h. The protective effects of nine cosmetic ingredients, including oat extract (S1), on the skin barrier were investigated based on the gene expression levels of aquaporin3 (AQP3), filaggrin (FLG), caspase-14 (CASP14), and human tissue kallikrein7 (KLK7), as well as those of various interleukins (IL) and vascular endothelial growth factor (VEGF). Results Among the nine ingredients, S1 had a good protective effect on the function of the skin barrier. It promoted the expression of AQP3, FLG, and CASP14, while inhibiting the expression of KLK7 in HaCaT cells, at a concentration of 0.06%. It also maintained IL-6, IL-8, and VEGF at appropriate levels while promoting the proliferation and differentiation of HaCaT cells. Conclusions The above indicators allow for the preliminary establishment of a method to evaluate the efficacy of the barrier protection ability of sensitive skin.

Modulation of Cell-Mediated Immunity to Suppress High Fat Diet-Induced Obesity and Insulin Resistance - Linna Yan; Kexiu Song; Mingming Gao; Shen Qu; Dexi Liu (Pharmaceutical Research, 2016)

Synthetic FXR Agonist GW4064 Prevents Diet-Induced Hepatic Steatosis and Insulin Resistance - Yongjie Ma; Yixian Huang; Linna Yan; Mingming Gao; Dexi Liu (Pharmaceutical Research, 2013)